2004
DOI: 10.1021/jp047994q
|View full text |Cite
|
Sign up to set email alerts
|

Role of Water in Transient Cytochrome c2 Docking

Abstract: Cytochrome c (cyt c) is a small water-soluble redox protein that facilitates electron transfer in photosynthesis and respiration by alternately docking to integral membrane proteins such as the photosynthetic reaction center (RC). Recently, a high-resolution X-ray structure was solved for the RC−cyt c 2 complex of Rhodobacter sphaeroides, revealing important contacts between the RC in its ground state and reduced cyt c 2 mediated by bridging water molecules. In this article, we compare the variations in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 39 publications
5
43
0
Order By: Relevance
“…Examples are (homologous yeast residues in parentheses) Arg-19 and Ala-87 in the complex of cyt c peroxidase and cyt c from yeast (6), and Ala-79 (Ala-87) in the complex of cyt c 552 with the Cu A domain of cyt c oxidase (30), Gln-14 (Arg-19) and Thr-36 (Val-34) in the cyt c 2 ⅐reaction center complex (7), as well as Thr-18 in the complex of yeast cyt c with the cyt f domain of the cyt b 6 f complex (40). The analogous cation-interaction of the reaction center⅐cyt c 2 complex has been observed as the most stable contact in molecular dynamic simulations (31,41). The core interface appears to be a central feature of the interaction of cyt c with many, structurally not related, binding partners.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Examples are (homologous yeast residues in parentheses) Arg-19 and Ala-87 in the complex of cyt c peroxidase and cyt c from yeast (6), and Ala-79 (Ala-87) in the complex of cyt c 552 with the Cu A domain of cyt c oxidase (30), Gln-14 (Arg-19) and Thr-36 (Val-34) in the cyt c 2 ⅐reaction center complex (7), as well as Thr-18 in the complex of yeast cyt c with the cyt f domain of the cyt b 6 f complex (40). The analogous cation-interaction of the reaction center⅐cyt c 2 complex has been observed as the most stable contact in molecular dynamic simulations (31,41). The core interface appears to be a central feature of the interaction of cyt c with many, structurally not related, binding partners.…”
Section: Discussionmentioning
confidence: 92%
“…Molecular dynamics simulations with the photosynthetic reaction center and cyt c 2 also indicated that the differences between the redox states are subtle. A structured cluster of water molecules was observed in the reduced cyt c 2 system, whereas fluctuations of water and residues at the interface increased upon oxidation (31). The authors suggested that the higher mobility may mediate the undocking process.…”
Section: Discussionmentioning
confidence: 97%
“…c 2 - bc 1 complex electrostatic interactions would be replaced by direct salt bridges. Purely for dielectric reasons these salt bridges would be 10-fold stronger than water-mediated interactions 27 making the bc 1 complex residence time of cyt. c 2 at least e 10 -fold longer and, thus, disrupting the overall efficiency of cyt.…”
Section: Discussionmentioning
confidence: 99%
“…1 has disclosed a fruitful area for examination, but falls far short of a complete picture of the influence of intracomplex dynamics on interprotein ET reactions. Among the issues to be addressed are the degree to which the addition of glycerol may be (i) changing the energy landscapes themselves, not merely the rates with which the landscapes are traversed (48), and (ii) influencing water activity (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%